Gerakan Feminisme Fujinkai dalam Perspektif Sejarah Perjuangan Perempuan di Indonesia - Aditia, Dimas; Lestari, Erika Sukma; Adelia, Dea Nuci; Arif, Suparman; Perdana, Yusuf (Universitas Hamzanwadi, 2022)
The Dutch defeat of its rule in the colonies ended the practice of colonialism and western-style imperialism. However, that does not necessarily make Indonesia immediately free and independent just like that. During the Japanese rule, various forms of propaganda were introduced, one of which was Fujinkai which was made at the beginning of the Japanese occupation of Indonesia. Fujinkai became a women's organization, significantly overshadowing all women's activities at that time. This study aims to study the Fujinkai Feminism Movement from the Perspective of the History of Women's Struggle in Indonesia. At the same time, there is also a line of supporters who participate in the Japanese tantara. The method used in this study is a historical method consisting of 5 stages: determination of topics, source collection (heuristic), source criticism, interpretation, and writing (historiography). The result of this research includes looking at Fujinkai's role in the history of Indonesian women's struggle in the field of Education and social activities, establishing relationships with Japan in the fields of arts and virtues, and sharpening science and skills training.Kekalahan Belanda atas kekuasaannya di daerah jajahan mengakhiri praktik kolonialisme dan imperialisme ala barat. Namun, hal itu tidak serta merta membuat Indonesia langsung merdeka dan merdeka begitu saja. Pada masa pemerintahan Jepang, berbagai bentuk propaganda diperkenalkan, salah satunya adalah Fujinkai yang dibuat pada awal pendudukan Jepang di Indonesia. Fujinkai menjadi organisasi wanita, yang secara signifikan menaungi semua aktivitas wanita saat itu. Penelitian ini bertujuan untuk mengkaji gerakan feminisme Fujinkai dari perspektif sejarah perjuangan perempuan di Indonesia. Pada saat yang sama, ada juga barisan pendukung yang ikut serta dalam tantara Jepang. Metode yang digunakan dalam penelitian ini adalah metode sejarah yang terdiri dari 5 tahap: penentuan topik, pengumpulan sumber (heuristik), kritik sumber, interpretasi, dan penulisan (historiografi). Hasil penelitian ini antara lain melihat peran Fujinkai dalam sejarah perjuangan perempuan Indonesia di bidang pendidikan dan kegiatan sosial, menjalin hubungan dengan Jepang dalam bidang seni dan kebajikan, serta mengasah ilmu pengetahuan dan pelatihan keterampilan.